Propolis Is an Efficient Fungicide and Inhibitor of Biofilm Production by Vaginal Candida albicans - Capoci, Isis Regina Grenier (Hindawi Publishing Corporation, 2015)

(untitled) (Evid Based Complement Alternat Med)
Vulvovaginal candidiasis (VVC) is one of the most common genital infections in women. The therapeutic arsenal remains restricted, and some alternatives to VVC treatment are being studied. The present study evaluated the influence of a propolis extractive solution (PES) on biofilm production by Candida albicans isolated from patients with VVC. Susceptibility testing was used to verify the minimum inhibitory concentration (MIC) of PES, with fluconazole and nystatin as controls. The biofilm formation of 29 vaginal isolates of C. albicans and a reference strain that were exposed to PES was evaluated using crystal violet staining. Colony-forming units were evaluated, proteins and carbohydrates of the matrix biofilm were quantified, and scanning electron microscopy was performed. The MIC of PES ranged from 68.35 to 546.87 μg/mL of total phenol content in gallic acid. A concentration of 546.87 μg/mL was able to cause the death of 75.8% of the isolates. PES inhibited biofilm formation by C. albicans from VVC. Besides antifungal activity, PES appears to present important antibiofilm activity on abiotic surfaces, indicating that it may have an additional beneficial effect in the treatment of VVC.